Control of Smart Aquarium Using Smartphone - Kurnia Aditama, Fauzan; Mukhaiyar, Riki (Department of Electrical Engineering Universitas Negeri Padang, 2024)
Effective water quality management is the key to maintaining a healthy and sustainable aquarium. The water quality in the aquarium affects the health of fish, plants, and other microorganisms, so it requires monitoring and control. Some water quality parameters that must be considered in ornamental fish aquariums are water pH, water turbidity, and water level in the aquarium. Along with the rapid development of technology, it is expected to make it easier for humans. This study aims to design an aquarium water quality control tool with control using a smartphone. In making this tool, Arduino is used as the control center. In addition, this tool also uses a pH sensor to measure the acidity level of water in the aquarium, uses a Turbidity sensor to measure the turbidity level of water in the aquarium and an Ultrasonic sensor to calculate the water level in the aquarium. The results of the sensor measurements will be displayed on the LCD screen and the Blynk application. The Blynk application display gets data from the NodeMCU ESP32 which is used to send sensor reading data to the Arduino online using the Internet Of Things (IoT). In addition to being used for monitoring, the Blynk application can be used to control water quality control pumps